Comparison of the energy needs a prescribed and administered enteral nutrition therapy in patients - Detregiachi, Claudia R.P.; Quesada, Karina R.; Marques, Dayane E. (Medicina (Ribeirao Preto), 2011)
Objective: evaluating the adequacy, prescription and energy supply of enteral nutrition therapy in hospitalized patients. Methods: was performed a retrospective survey of the evolution of TNE protocol of 59patients hospitalized in a general hospital in Marília / SP / BR. Data collected included gender, age,clinical diagnosis, anthropometric and dietary data related to the prescribed dietary formula, route andmethod of administration of the enteral nutrition, the daily volume prescribed and administered, the dailyamount of energy required and offered in the diet, as well as possible complications. Body mass index(BMI), triceps skinfold (TSF) and arm muscle circumference (AMC) were used to establish the nutritionalstatus of the patients. The adequacy of ENT was done according to the daily energy requirement compared to the average energy received during the daily use of ENT. Results: The average found to the BMIwas 21.4 kg/m2, and no differences were found comparing male and female. The data for TSF and AMCwere different between genders (p<0.05) and suggest a more severe muscle mass in relation to adipose tissue.The averaged to the energy requirements was 1642 kcal/day but the average of energyprescribed was 1045 kcal/day and the amount offered was 1035 kcal/day. There was a significant difference between the necessity and the supplied energy offered through enteral nutrition (p=0.00) as wellbetween the energy required and prescribed (p =0.00), both were shorter than the necessity. There wasno significant difference (p>0.05) in energy supply, volume of enteral nutrition prescribed and administered among eutrophic, underweight or overweight patients. Conclusion: The results of this study indicate that the prescription and energy supply were not based on the needs of these patients, causing asignificant energy deficit, which can lead to worsening of the nutritional status of the same. In hospitalizedpatients in use of ENT, the energy requirement must be made by a qualified professional within themultidisciplinary team, based on the needs of each patient.